PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN BANYUMANIK SEMARANG - Rahmat Adhim Rifai, 10.05.51.0089 (Students Journal of Economic and Management, 2015)
This study aimsto analyzethe influence ofLeadership, MotivationandCulture Organizationon Employee PerformanceOffice of Sub-district Banyumanik Semarang.The populationin this studyis thetotal numberof employeesamounted to50respondents. The data usedare primary data, that is dataobtained directlyfrom the source. The techniqueusedforprimary data collectionis donebymeans ofquestionnaires to therespondents. The hypothesis test indicate that Leadershiphas apositive and significant impacton employee performance, Motivationhas apositiveand significant impact onemployee performance, and Culture Organization has apositive and significant impacton employee performance. Keywords: Leadership, Motivation, Culture Organization and Employee Performance.